2017
DOI: 10.5114/wiitm.2017.70323
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid appendectomy with classic trocar on McBurney's point.

Abstract: Introduction Appendectomy is still the most commonly performed intra-abdominal operation worldwide. Interestingly, it has not reached the same popularity as other laparoscopic surgical procedures. Although multiple techniques have been described, a standard approach has not been described for the laparoscopic technique yet. Aim To perform hybrid appendectomy for acute appendicitis on McBurney’s point, aiming to perform an easier and quicker procedure while limiting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…[9] Several previously published studies showed that LAs are feasible and beneficial, producing a shorter length of stay (LOS), reduced pain, decreased surgical site infection rate, shorter postoperative ileus, and a better cosmetic effect. [10,11] Moreover, LA has been shown to be safer in complicated AA than in open surgery; therefore, its use in the emergency setting is rising. [12][13][14][15][16] While challenging, discrimination between uncomplicated and complicated AA is clinically relevant as outcomes vary, with complicated cases faring worse.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Several previously published studies showed that LAs are feasible and beneficial, producing a shorter length of stay (LOS), reduced pain, decreased surgical site infection rate, shorter postoperative ileus, and a better cosmetic effect. [10,11] Moreover, LA has been shown to be safer in complicated AA than in open surgery; therefore, its use in the emergency setting is rising. [12][13][14][15][16] While challenging, discrimination between uncomplicated and complicated AA is clinically relevant as outcomes vary, with complicated cases faring worse.…”
Section: Introductionmentioning
confidence: 99%
“…In all of the cases, the CO2 was drawn from the right subphrenic space, and low-pressure pneumoperitoneum was performed. This was done in addition to minimal tissue handling and trauma, both of which contribute to a reduction in the perception of pain [11,12,13] . In addition, the shoulder pain that was caused by the remaining gas irritation was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional open surgery, laparoscopic appendectomy offers several advantages, including shorter hospital stays, faster return to normal activities, reduced pain levels, and improved cosmetic outcomes. Acute appendicitis, which is characterized by acute inflammation of the appendix, is a common surgical emergency with a lifetime incidence of approximately 8% [9,10,11] . The goal of this study is to assess the role of laparoscopy in the treatment of difficult appendicitis by analyzing factors such as operating time, intra-operative complications, length of hospital stay, analgesic use, time to return to oral eating, and postoperative risks.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic appendectomy (LA) became a popular surgical procedure recently, now accounting for 38.1% of all appendectomies [ 2 , 3 ]. Fewer wound infections and hospitalization days, less postoperative pain, faster recovery and better cosmetic results are the accepted advantages of LA compared to open conventional appendectomy [ 4 8 ].…”
Section: Introductionmentioning
confidence: 99%